2022
DOI: 10.1186/s12864-022-08793-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two new QTLs of maize (Zea mays L.) underlying kernel row number using the HNAU-NAM1 population

Abstract: Background Maize kernel row number (KRN) is one of the most important yield traits and has changed greatly during maize domestication and selection. Elucidating the genetic basis of KRN will be helpful to improve grain yield in maize. Results Here, we measured KRN in four environments using a nested association mapping (NAM) population named HNAU-NAM1 with 1,617 recombinant inbred lines (RILs) that were derived from 12 maize inbred lines with a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…The authors also found that only a few QTLs overlap with previously reported loci, and they proposed that this may be due to different parents being used for the construction of the mapping population, and epistasis might modulate the effect of a QTL depending on the genetic background [21]. KRN is one of the most important ear trait components and an important selection target during maize domestication and breeding [13,14,30,31]. Many efforts have been made to dissect the genetic basis of KRN and more than three hundred QTLs have been identified [13,[30][31][32][33][34], and at least four of the KRN QTLs have been cloned [35][36][37][38].…”
Section: The Genetic Basis Of the Ear Traits And Summary Of The Genet...mentioning
confidence: 95%
See 2 more Smart Citations
“…The authors also found that only a few QTLs overlap with previously reported loci, and they proposed that this may be due to different parents being used for the construction of the mapping population, and epistasis might modulate the effect of a QTL depending on the genetic background [21]. KRN is one of the most important ear trait components and an important selection target during maize domestication and breeding [13,14,30,31]. Many efforts have been made to dissect the genetic basis of KRN and more than three hundred QTLs have been identified [13,[30][31][32][33][34], and at least four of the KRN QTLs have been cloned [35][36][37][38].…”
Section: The Genetic Basis Of the Ear Traits And Summary Of The Genet...mentioning
confidence: 95%
“…KRN is one of the most important ear trait components and an important selection target during maize domestication and breeding [13,14,30,31]. Many efforts have been made to dissect the genetic basis of KRN and more than three hundred QTLs have been identified [13,[30][31][32][33][34], and at least four of the KRN QTLs have been cloned [35][36][37][38]. A significant amount of information on the genetic basis for the most important ear traits has accumulated, which provides a solid basis for combining the different individual studies to summarize the genetic regulation of ear traits.…”
Section: The Genetic Basis Of the Ear Traits And Summary Of The Genet...mentioning
confidence: 99%
See 1 more Smart Citation
“…A GWAS study revealed 31 associated SNPs representing 17 genomic loci with effects in at least one of the five individual environments. In another study, Fei et al [ 24 ] utilized a nested association mapping (NAM) population consisting of 1617 RILs and identified five QTLs related to KRN via joint linkage mapping (JLM). These QTLs were further validated through linkage mapping (SLM) and GWAS.…”
Section: Introductionmentioning
confidence: 99%